Renal transplantation-related risk factors for the development of uterine adenomatoid tumors - Mizutani, Teruyuki (Gynecol Oncol Rep, 2016)
• We analyzed the epidemiological factors for clinical manifestations of uterine adenomatoid tumors. • Renal transplantation with immunosuppression therapy is risk factor for the development of uterine adenomatoid tumors. • The length of time on dialysis is risk factor for the development of uterine adenomatoid tumors.